2002
DOI: 10.1038/ncb748
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein is phosphorylated in synucleinopathy lesions

Abstract: The deposition of the abundant presynaptic brain protein alpha-synuclein as fibrillary aggregates in neurons or glial cells is a hallmark lesion in a subset of neurodegenerative disorders. These disorders include Parkinson's disease (PD), dementia with Lewy bodies (DLB) and multiple system atrophy, collectively referred to as synucleinopathies. Importantly, the identification of missense mutations in the alpha-synuclein gene in some pedigrees of familial PD has strongly implicated alpha-synuclein in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
1,805
6
20

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,825 publications
(1,892 citation statements)
references
References 24 publications
61
1,805
6
20
Order By: Relevance
“…We found no difference in specificity whether we used O/P‐aSyn‐Ab. Although phosphorylation is generally considered a marker of choice to delineate pathological aggregates from normal, native aSyn accumulation 35, using the P‐aSyn‐Ab, Bottner et al . 17 and Visanji et al .…”
Section: Discussionmentioning
confidence: 99%
“…We found no difference in specificity whether we used O/P‐aSyn‐Ab. Although phosphorylation is generally considered a marker of choice to delineate pathological aggregates from normal, native aSyn accumulation 35, using the P‐aSyn‐Ab, Bottner et al . 17 and Visanji et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of a-synuclein aggregates extracted from brains affected by rare neurodegenerative diseases related to PD, provide tantalizing evidence that pore-like structures do exist in vivo. Several studies of a-synuclein fibrils from diffuse Lewy body disease (DLBD) reveal pore-like structures that co-purify with a-synuclein fibrils (Spillantini et al 1998a ;Fujiwara et al 2002). The resemblance of these structures to the amyloid pores produced from a-synuclein in vitro (Lashuel et al 2002a) is striking.…”
Section: Testing the Amyloid Pore Hypothesis By Attempting To Disprovmentioning
confidence: 99%
“…In relation to α ‐synucleinopathies in particular, PP2A catalyzes the dephosphorylation of phospho‐Ser 129 α ‐synuclein, and the methylation state of the PP2A C subunit regulates this activity 13. Accordingly, the finding of decreased PP2A methylation in this study provides a molecular mechanism for the reduced PP2A activity reported in α ‐synucleinopathies 16 and is likely a significant contributor to the hyperphosphorylation of aggregated α ‐synuclein in these disorders 10, 29…”
Section: Discussionmentioning
confidence: 53%
“…Pathologic α ‐synuclein accumulation itself may be an inhibitor of PP2A activity resulting in a vicious cycle exacerbating the hyperphosphorylation and aggregation of pathogenic proteins including α ‐synuclein and tau in Lewy body disease 10, 45. Overexpression of α ‐synuclein, particularly its A53T mutant which causes dominantly inherited PD and dementia, increases intracellular levels of reactive oxygen species in SH‐SY5Y neuroblastoma cells ,46 contributing to oxidative stress‐mediated dysregulation of PP2A 42, 44.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation